Resource-Efficient Low-Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation - Tan, Deming; Kirbus, Benjamin; Ruesing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M. (Small, 2020)
Optically nonlinear Pb2B5O9X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo-) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low-cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb2B5O9X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite-like borate halide structure. Thorough examinations using powder X-ray diffraction and scanning electron microscopy, the Pb2B5O9X microcrystals are indicated to be chemically pure and single-phased. Besides, the Pb2B5O9X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low-temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo-) catalysis investigations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: borates; ionothermal synthesis; second harmonic generation; second harmonic generation microscopy; surface second harmonic generation